Not Only the Market - Potůček, Martin (Book collections on Project MUSE., 1999)
"Successful transition for any postcommunist country is reliant upon market, government and the civic sector. Potucek's pioneering study of the Czech Republic highlights the early transitional mistakes made with respect to the role of these sectors." "Not Only the Market examines the balance between these sectors, and makes useful comparisons with other postcommunist countries. Focusing on developmental issues, the book looks at a number of public concerns including social and health care reform, privatization and the emerging patterns of corporatism." "Potucek provides a blueprint for reform which emphasizes the necessity of a conscious public policy to optimize freedom while still addressing issues of inequality."--Jacket.